Reduction of Pollutants in Two Stroke Petrol Engine - Krishna, M. V. S. Murali; Janardhan, N.; Kumar, S. Narasimha; Kishor, K.; Priyadarsini, Ch. Indira; Nagini, Y. (Advanced Aspects of Engineering Research Vol. 9, 2021)
Carbon mono oxide (CO) and un-burnt hydrocarbons (UBHC) are the exhaust emissions from petrol engine and inhaling of these emissions cause health. They also cause impact on environment. If the engine is run with alcohol, aldehydes have to be checked also. Hence control of these pollutants is an immediate effect. These emissions can be controlled by making changes in design of combustion chamber, the fuel composition and with the provision of the catalytic converter. Copper of thickness 300 microns was coated over piston crown, inside portion of cylinder liner and cylinder head of the two- stroke 2.2 kW petrol engine at the rated speed of 3000 rpm fuelled with gasohol (blend of 20% ethanol and 80% gasoline by volume) with the provision of catalytic converter with different catalysts such as sponge iron and manganese ore with air injection. The influence of parameters of mass of the catalyst, air flow rate and brake mean effective pressure of the engine on the emissions were studied. A microprocessor-based analyzer was used for the measurement of CO/UBHC in the exhaust of the engine. Aldehydes were measured by wet method. Catalytic parameters were found to show strong influence on reduction of the pollutants in the exhaust. Copper coated spark ignition engine (CCE) with gasohol operation reduced the exhaust emissions considerably when compared to conventional engine (CE) with neat gasoline operation.